# trig

tanx = 5/12 and sinx<0

Find sin2x and cos2x

How to get the answers of sin2x = 120/169 and cos 2x = 119/169?

1. 👍 1
2. 👎 0
3. 👁 411
1. tanx = 5/12

r^2 = x^2 + y^2
= 12^2 + 5^2
r = 13

tanx >0 and sinx<0, so x must be in quad. III and
and sinx = -5/13 , cosx = -12/13

sin 2x = 2sinxcosx = 2(-5/13)(-12/13)
= 120/169
cos 2x = cos^2 x - sin^2 x
= 144/169-25/169
=119/169

do the others the same way, or the way
drwls showed you in the other post.

1. 👍 0
2. 👎 0
2. tan x = 13 cot x

1. 👍 0
2. 👎 0
3. tan x = 13 cot x
tan x = 13/tan x
tan^2 x = 13
tan x = ±√13
x = 74.5º,105.5º, 254.5º, 285.5º

1. 👍 0
2. 👎 0

## Similar Questions

1. ### Maths

If is a n acute angle and tanx=3 4 evaluate cosx-sinx cosx+sinx

2. ### Pre-Calculus

Find a numerical value of one trigonometric function of x if tanx/cotx - secx/cosx = 2/cscx a) cscx=1 b) sinx=-1/2 c)cscx=-1 d)sinx=1/2

3. ### TRIGONOMETRY *(MATHS)

Q.1 Prove the following identities:- (i) tan^3x/1+tan^2x + cot^3x/1+cot^2 = 1-2sin^x cos^x/sinx cosx (ii) (1+cotx+tanx)(sinx-cosx)/sec^3x-cosec^3x = sin^2xcos^2x.

4. ### maths

proof that tanx + secx -1/tanx - secx+1 = 1+sinx/cosx

1. ### precal

1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-secx =(sinx/cosx)+ (1/cosx)+(sinx/cosx)-(1/cosx) =sinx/cosx+ sinx /cosx= -2tanxI but I know this can't be correct because what I did doesn't end as a

2. ### Math

How do I solve this? tan^2x= 2tanxsinx My work so far: tan^2x - 2tanxsinx=0 tanx(tanx - 2sinx)=0 Then the solutions are: TanX=0 and sinX/cosX = 2 sin X Divide through by sinX: we have to check this later to see if allowed (ie sinX

3. ### math

tanx+secx=2cosx (sinx/cosx)+ (1/cosx)=2cosx (sinx+1)/cosx =2cosx multiplying both sides by cosx sinx + 1 =2cos^2x sinx+1 = 2(1-sin^2x) 2sin^2x + sinx-1=0 (2sinx+1)(sinx-1)=0 x=30 x=270 but if i plug 270 back into the original

4. ### math

Trig Identities prove sinx+1 \ 1-sinx = (tanx+secx)^2

1. ### Pre-Calc

How to simplify secx(sinx/tanx)?

2. ### Math Trigonometric Identities

1/sinx - sinx = cosx/tanx

3. ### Trigonometry Check

Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] = [cosx-((1)cosx-(0)sinx)sinx]/[cosx-((-1)cosx+(0)sinx)tanx] = [cosx-cosxsinx]/[cosx+cosxtanx] =

4. ### maths - trigonometry

I've asked about this same question before, and someone gave me the way to finish, which I understand to some extent. I need help figuring out what they did in the second step though. How they got to the third step from the